WILLINGNES TO PAY SUNGAI TAMBAN MUARA KECAMATAN TAMBAN KABUPATENBARITO KUALA - RAISA NOOR (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2018)
Raisa Noor, a Willingnes to Pay Tamban River Estuary Barito Kuala Regency Tamban Subdistrict. Under the guidance of Yunita Sopiana, SE, MSE.            The purpose of research it is (1) find out the assesment of the community around the River toward of the assesment mouthof the river ecosystem State Tamban Barito Kuala Regency Tamban Subdistrict. (2) knowing the value of the community’s willingnes to pay ( willingnes to pay) for the benefit of river ecosystem Tamban Estuary.            This research is a descriptive qualitative research using primary and secondary data are data from the office of the Chief of the village Tamban, in the form of questionnaires and so forth.            From the result of the community assesment and quality conditions of the River estuary Tamban declined, although river water is unfit for consumption, but some people still depend onriver water Tamban Estuary. The River Estuary u.s Tamban water transportation is already limited. Poor water quality of the River Estuary Tamban ismainly caused by industrial activity and high his intensive use u.s water transportation. The occurrence of shifting values and water quality of the River Estuary Tamban in the end make an unhealty environment for the people that use river water Tamban Estuary. Particularly the communities along the river basin Jl based the calculation od derived Community willingnes to pay ( willingnes to pay) from the mouth of the river ecosystem Tamban amounting to Rp. 133,040,000,-. Result from the Division of the total WTP and the number of population the average WTP of this Idr 80.000 per head of the family.Keyword: Willingnes To Pay River, Population